Climate Change Adaptation of Alpine Ski Tourism in Spain - Luís Campos Rodrigues; Jaume Freire-González; Aina González Puig; Ignasi Puig-Ventosa (Climate, 2018)
Mountain ecosystems are considered to be vulnerable to climate change, with potential detrimental effects including the reduction of the snow seasons, the gradual retreat of glaciers, and changes in water storage and availability. One vulnerable sector to climate change is winter tourism, with some resorts likely to experience a significant reduction in the length of the skiing seasons and snow recreation areas throughout this century. This study assessed the vulnerability of 31 Spanish alpine ski resorts to climate change and evaluated the potential socio-economic and environmental implications of several adaptation measures. Results show that lower-altitude areas such as the Cantabrian Mountains and the Iberian System could be more vulnerable to climate change than higher-altitude areas of the Catalan Pyrenees or the Penibaetic System. Adaptation initiatives may include, inter alia, the production of artificial snow, the protection and conservation of the snow coverage area, and the diversification of recreation activities offered during the whole year. The study concludes that the design and implementation of adaptation strategies have to be adequate to the level of vulnerability associated with each resort as well as minimize their potential socio-economic and environmental costs.
Keywords: 330